Hubungan antara Ekspresi P16 dengan Respon Histologik Kemoterapi Neoadjuvan pada Osteosarkoma Konvensional - Dian Sari Oethia Vathonati; Nurjati Chairani Siregar; Puspita Eka Wuyung (Majalah Patologi Indonesia, 2021)
BackgroundOsteosarcoma is the most common primary malignant bone tumor in children and young adult. Its pathogenesis has been linked toalterations in several genes. The high percentage is found involving Retinoblatoma (RB) pathway. p16 plays as a tumor suppressorin RB pathway to controll proliferation of the tumor cell. The degree of neoadjuvan chemotherapy histological necrosis response isrelated to prognosis of patients with osteosarcoma. Chemotherapy and p16 both synergic in inhibit the cell tumor proliferation andsupport apoptotic. Loss of p16 function is related to progressiveness of the tumor. The aim of this study was to investigate therelationship of p16 expression in pretreatment osteosarcoma to pathologic necrotic histological response after neoadjuvanchomotherapy.MethodsThis is a cross sectional study p16 stainning was done and count the positive expression tumor cell in percentage. Positive wasdefined as strong and medium nuclear stainning in 30% or greater. The samples is catagorized into positive and negative expressionthen it is correlated into tumor necrotic area based on grade of Huvos.ResultsSamples consist of 33 cases. Positive stainning was found in 10 cases (30.3%), 6 of 10 cases had good chemotherapy response.Negative stainning was found in 23 cases and 21 of 23 cases had poor chemotherapy response. A significant association was notedbetween p16 expression and histological necrotic response to neoadjuvan chemotherapy (p=0.004).ConclusionThe result showed that p16 expression associate significantly with histological necrotic response to neoadjuvan chemotherapy inconventional osteosarcoma (p=0.004).